Nuclear-wave-packet quantum interference in the intense laser dissociation of the D2+ molecule - Halász, Gábor J.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2013)
Recently it has been recognized that electronic conical intersections in molecular systems can be induced by laser light even in diatomics. As is known a direct consequence of these accidental degeneracies is the appearance of nonadiabatic effects which has a strong impact on the nuclear quantum dynamics. Studying the photodissociation process of the D2+ molecule, we report here some observable quantum interference phenomena that arise from the topological singularity induced by a strong laser field.
Im Titel ist die Zahl "2" tiefgestellt und das Zeichen "+" hochgestellt
Gesehen am 25.02.2021